2021
DOI: 10.26633/rpsp.2021.144
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent pregnancy, public policies, and targeted programs in Latin America and the Caribbean: a systematic review

Abstract: Objective. To present and assess evidence from Latin America and the Caribbean (LAC) on public policies and targeted programs which may have influenced variations in adolescent pregnancy or its proximate determinants, and to identify knowledge gaps that require further research. Methods. A systematic review was performed based on the 2015 PRISMA protocol. Five databases were searched for articles published between 2000 and 2019 that refer to at least one country in LAC. The outcomes of interest were adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
2
10
0
2
Order By: Relevance
“…An evaluation of the adolescent pregnancy rate was also carried out, represented in the number of pregnancies per thousand women between 15 and 19 years of age in Peru, Haiti, Colombia, Bolivia, Nicaragua, which again coincides with what was reported in the study by Pleson et al [8] where a rate of adolescent pregnancies in Centroa which again coincides with what was reported in the study by Pleason et al [8]; Figure 1 representing this last region the highest values compared to the average for the Latin American region and being much higher than the world average, for which it is considered that Latin America is the only region with a growing trend of adolescent pregnancies [21,22]. According to Rodriguez [23] it is estimated that 16% of fertility among women is given by adolescents between 15 and 19 years of age in Latin America, but despite this it can be established see that at the local level there are countries like Colombia where it is estimated that at least 23% of children are the product of adolescent mothers [24]; In Peru, approximately 30.5% of women between the ages of 15 and 19 have had at least one child or were pregnant in 2017, despite this, Sanchez and Favara state that in the same period of time this percentage was 14.3%. It is possible to deduce from this that in the Latin American and Caribbean region adolescent pregnancies are a growing problem, in addition that there is a limitation to access to information, since the statistics do not include pregnant adolescents who had abortions.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…An evaluation of the adolescent pregnancy rate was also carried out, represented in the number of pregnancies per thousand women between 15 and 19 years of age in Peru, Haiti, Colombia, Bolivia, Nicaragua, which again coincides with what was reported in the study by Pleson et al [8] where a rate of adolescent pregnancies in Centroa which again coincides with what was reported in the study by Pleason et al [8]; Figure 1 representing this last region the highest values compared to the average for the Latin American region and being much higher than the world average, for which it is considered that Latin America is the only region with a growing trend of adolescent pregnancies [21,22]. According to Rodriguez [23] it is estimated that 16% of fertility among women is given by adolescents between 15 and 19 years of age in Latin America, but despite this it can be established see that at the local level there are countries like Colombia where it is estimated that at least 23% of children are the product of adolescent mothers [24]; In Peru, approximately 30.5% of women between the ages of 15 and 19 have had at least one child or were pregnant in 2017, despite this, Sanchez and Favara state that in the same period of time this percentage was 14.3%. It is possible to deduce from this that in the Latin American and Caribbean region adolescent pregnancies are a growing problem, in addition that there is a limitation to access to information, since the statistics do not include pregnant adolescents who had abortions.…”
Section: Resultssupporting
confidence: 90%
“…Based on the identification of risk and predisposing factors for adolescent pregnancy, research has been carried out such as that carried out by Favara [13] in which it is shown that in Chile an increase in the school day leads to a reduction of 3 % of adolescent pregnancies since adolescents have a greater awareness of planning methods, consequences of pregnancy, responsible decision-making and a greater educational and professional aspiration. In favor of this position is Rodriguez [23] who carried out a systematic review in which he highlights that "forcing women to spend more time in school significantly reduces the probability of maternity in adolescence" and regarding the reasons why which this decrease occurs, agrees with Favara.…”
mentioning
confidence: 90%
“…In some countries that have CSE programs, there is a lack of human and material resources allocation planning (29) (30). Gaps between legislation and effective access to SRMHR services include, among others, the limited access to contraceptive methods in some groups (e.g., adolescents) (31), lack of access to EC (due to lack of supplies or reluctance of professionals to provide it even in cases of sexual violence); lack of access to treatments for transgender population; among other (32)…”
Section: Discussionmentioning
confidence: 99%
“…Para la población adolescente, es especialmente importante abordar los estereotipos, prejuicios y valores relacionados con el sexo, la reproducción y las relaciones de pareja y familiares, que perpetúan relaciones complejas entre los sexos y promueven conductas de riesgo. Por otro lado, es claro que la divulgación de información por sí sola no es suficiente para desarrollar habilidades sociales que estimulen condiciones que aseguren una toma de decisiones y una práctica sexual sana, libre, satisfactoria y gratificante en esta etapa de la vida [3].…”
Section: Políticas Públicas Y El Rol De Enfermeríaunclassified
“…El cuidado de enfermería durante el proceso de gestación debe ir más allá del cumplimiento o la aplicación de la Ruta de Atención Integral Materno Perinatal. Este cuidado se concibe como "la interacción que se ejerce entre la enfermera, la gestante, su hijo por nacer y la familia, donde comparten conocimientos, experiencias, habilidades y precepciones acerca del cuidado, generando compromisos para mantener la salud y calidad de vida" [3]. En consecuencia, es importante establecer una relación terapéutica entre profesional de enfermería, paciente y familia, en función de permitir que el profesional establezca un plan de cuidados acorde con las necesidades reales de la gestante, con el fin de asegurar un curso adecuado del embarazo [3].…”
Section: Introductionunclassified